Kaji tindak program IDT 1994-1996 - Mubyarto; Masyarakat Perhutanan Indonesia; Indonesia. Badan Perencanaan Pembangunan Nasional (Jakarta : Aditya Media, 1996)
Evaluation of government program to all alleviate proverty in villages in the 27 provinces of indonesia
Keywords: Community development -- Indonesia; Community development -- Indonesia -- Evaluation; Proverty -- Indonesia